Training of explosive force in university volleyball players - Yordan Portela-Pozo; Elizabeth Rodriguez-Stiven; Armando Peréz-Fuentes (Universidad de Guantánamo, 2019)
The objective of the study is to verify the effect of 8 weeks of training on the lower train using the plyometric method and the combined method with overload and its relation with jumping ability. The sample is of 16 university volleyball players, divided into two groups, the plyometric and the overload. The power of the lower train is evaluated with counter movement and Abalakov. The Shapiro-Wilk significance test and the T-student test were used for independent samples. The plyometric method was more effective than the overload method.